Same bed different dreams : a novel - Park, Ed, 1970- (Random House, 2023)
"March 1919. Far-flung Korean patriots establish the Korean Provisional Government to protest the Japanese occupation of their country. This government-in-exile proves mostly symbolic, its petitions ignored by heads of state as Korea's nationhood is erased. After Japan's defeat in World War II, the KPG dissolves and civil war erupts, resulting in the North-South split that remains today. But what if the KPG still existed now, today--working toward a unified Korea, secretly harnessing the might of a giant tech company to further its aims? That's the outrageous premise of Same Bed Different Dreams, which spins Korean history, American pop culture, and our tech-fraught lives into an extraordinary and unforgettable novel. Weaving together three distinct narrative voices, Park twists reality like a kaleidoscope, forging connections and reinterpreting the past. Early on we meet Soon Sheen, who works at the sprawling international technology company GLOAT, and comes into possession of an unfinished book authored by the KPG. The manuscript is a mysterious, revisionist history, tying famous names and obscure bit players to the KPG's grand project. This strange manuscript links together figures from architect-poet Yi Sang to Jack London to Marilyn Monroe. M*A*S*H is in here, too, and the Moonies, and a history of violence extending from the assassination of President McKinley to the Soviet downing of Korean Air Lines Flight 007"--